2018
DOI: 10.3390/molecules23102596
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Prebiotic Potential of Longan Juice Obtained by Enzymatic Conversion of Constituent Sucrose into Fructo-Oligosaccharides

Abstract: The prebiotic potential of longan juice obtained by a commercial Viscozyme L for conversion of constituent sucrose to fructo-oligosaccharide was investigated. The physicochemical properties and carbohydrate composition of the longan juice was evaluated before and after enzymatic treatment. The stimulation effects of the treated longan juice on probiotic bacteria growth were also studied in vitro. The results showed that total soluble solids, yield and clarity of longan juice were all significantly improved aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 41 publications
1
7
1
1
Order By: Relevance
“…In the hypothetical situation where AMS was decreased to the similar level of 2.98 ± 0.02 mg/g fresh longan fruit for the current batch of FLJ‐C possessing lower level of total sugar composition (40.4 ± 0.3 mg/g fresh longan fruit) with C/N molar ratio of 21.88 ± 0.20, the recalculated ratio could be shifted down to 30.83 ± 0.31 compared to the tabulated value of 39.07 ± 0.54. In fact, FLJ‐C in the current study had the mass ratio (sucrose:glucose:fructose) of (3.46–3.78:1.08–1.12:1) compared with Nunta et al () who reported 2.17:1.17:1 and Chen, Lan, Zhao, Wang, and Hu () with mass ratio of 3.97:1.32:1 using longan fruit (probably assorted grade) obtained from Gaozhou, Guangdong province, China. The different level of initial total sugar composition and/or mass ratio of individual sugars could influence the metabolism pathway of microbes even when C/N molar ratio was kept constant as described by Ginesy, Rusanova‐Naydenova, and Rova ().…”
Section: Resultscontrasting
confidence: 51%
“…In the hypothetical situation where AMS was decreased to the similar level of 2.98 ± 0.02 mg/g fresh longan fruit for the current batch of FLJ‐C possessing lower level of total sugar composition (40.4 ± 0.3 mg/g fresh longan fruit) with C/N molar ratio of 21.88 ± 0.20, the recalculated ratio could be shifted down to 30.83 ± 0.31 compared to the tabulated value of 39.07 ± 0.54. In fact, FLJ‐C in the current study had the mass ratio (sucrose:glucose:fructose) of (3.46–3.78:1.08–1.12:1) compared with Nunta et al () who reported 2.17:1.17:1 and Chen, Lan, Zhao, Wang, and Hu () with mass ratio of 3.97:1.32:1 using longan fruit (probably assorted grade) obtained from Gaozhou, Guangdong province, China. The different level of initial total sugar composition and/or mass ratio of individual sugars could influence the metabolism pathway of microbes even when C/N molar ratio was kept constant as described by Ginesy, Rusanova‐Naydenova, and Rova ().…”
Section: Resultscontrasting
confidence: 51%
“…Analysis of chromaticity revealed the decrease in the L value and the increase in a, b, and △E values after the production of oligosaccharides. This trend was consistent with the report by Cheng et al (2018), who used enzymes to convert longan juice sugar into oligosaccharides. Preserved yuzu had lower pH value (3.82) but higher acidity (1.31 ± 0.03%), soluble solids (34.5 ± 0.00 °Bx), and viscosity than sucrose.…”
Section: Physicochemical Characteristicssupporting
confidence: 93%
“…The results of content determination showed that the content of water-soluble LPs obtained from the enzymatically treated extracts increased significantly from 3.61 to 8.30 mg/g, while the insoluble fiber content decreased significantly with increasing enzymatic digestion time. This was because during enzymatic digestion, a large amount of insoluble fiber could be hydrolyzed into oligomers, which are recycled into the water-soluble LPs group ( 13 ). However, enzymatic digestion of LPs has some disadvantages, such as some enzymes are expensive and not easily available; strict control of temperature and pH is required during the experimental process, and changes in conditions may lead to inactivation of the enzymes; and may also destroy the advanced structure of some LPs.…”
Section: Methods Of Extraction and Purificationmentioning
confidence: 99%
“…In conclusion, the content and molecular size distribution of LPs in longan juice changed significantly after enzyme treatment, implying that enzymes modify the structure of LPs and thus affect the expression of their biological activities. These showed the good potential of enzyme-treated LPs as functional foods, nutraceuticals and dietary prebiotics ( 50 ).…”
Section: Structural Featuresmentioning
confidence: 99%